Design of a low power desktop wireless charging station - Li, Xiang (Nanyang Technological University, 2024)
ith the development of integrated circuits, the size of modern smart products has gradually decreased. Simultaneously, ease of portability has become one of the standards for electronic product design. The power supply for such portable electronic products generally comes from internal lithium-ion batteries. Due to the limited capacity of batteries, smart electronic products need to be frequently recharged. However, traditional wired charging methods are constrained by power sources and are prone to damage to charging interfaces. Therefore, designing a reliable wireless charging solution has become a requirement in the modern market. This design will be based on a wireless power transmission system, combined with magnetic coupling resonance technology and the QI protocol, to develop a wireless power transmission circuit suitable for low-power electronic devices. This dissertation comprehensively studies the principles, basic communication structures, circuit structures, and operational structures of wireless charging technology. It aims to design a low-power wireless power transmission system to provide some references and insights for future wireless charging systems. The document first discusses several inverter structures, providing technical support for the wireless power transmission end. It adopts the full-bridge inverter structure as the circuit topology, combined with the SW3526 chip to form a QI protocol buck circuit, capable of achieving a 65W fast charging output interface. Meanwhile, it utilizes SW3526+IP6826 to construct a QI protocol single-coil drive circuit, capable of achieving a wireless charging output capability of 15W. The main focus of this design lies in the hardware circuit structure, aiming to improve the efficiency of wireless power transmission, reduce system temperature rise, enhance system stability, and increase system compatibility to meet the changing needs of the vast majority of wireless charging devices currently available on the market.